Semiconductor oxide based gas sensors - Cao, Wen Qing (2008)
Currently, the synthesis of new materials, including nano-sized material, for the gas sensing applications and the basic understanding of the sensing mechanism and principle are emphasized in this thesis via the study of solid solution of mixed zirconium oxide and iron oxide for the application of gas sensing.